2017
DOI: 10.15388/klbt.2016.10365
|View full text |Cite
|
Sign up to set email alerts
|

Evidence (re)presentation and evidentials in popular and academic history: facts and sources speaking for themselves

Abstract: The paper pivots around the different roles of evidentials and the different ways in which evidence is represented in the discourse of popular and academic history, thereby exploring the dynamics of both genres from a discourse analytical perspective. The analysis is based on two corpora of academic and popular articles on history. In particular, it is focused on those lexico-grammatical resources for tracing the speaker’s source and mode of information that constitute the distinguishing features of the two ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Therefore, the use of evidentials may be unnecessary or does not fit the informal tone of the discussion forum. This adjustment suggests that students are actively making decisions about what should be included in their writing to convince their predicted audience to agree with their propositions; this is consistent with previous findings on audience awareness (Warschauer and Grimes, 2007) and critically selecting evidence to serve the intention of the writer (Bondi and Sezzi, 2017).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, the use of evidentials may be unnecessary or does not fit the informal tone of the discussion forum. This adjustment suggests that students are actively making decisions about what should be included in their writing to convince their predicted audience to agree with their propositions; this is consistent with previous findings on audience awareness (Warschauer and Grimes, 2007) and critically selecting evidence to serve the intention of the writer (Bondi and Sezzi, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…The type of evidence presented in a text can be a marker of a genre (Hyland, 2005;Khedri, 2018) and, thus, the use of evidence in academic writing also indicates familiarity, expertise and belonging in the field. Bondi and Sezzi (2017) concluded that the forms of citations used in writing have to serve the intended purpose of the writer. They differentiated the effects of foregrounding different elements of previous research, either the proposition used in previous research or the researcher(s).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of metadiscourse devices in academic and technical texts is undeniable, as put forward in Mauranen (1993), Hyland (1998Hyland ( , 2005, Hyland and Tse (2004) and Mur Dueñas (2011), among others. Examples from either a diachronic or a synchronic perspective include Alonso-Almeida (2012; Alonso-Almeida and Álvarez-Gil (2019); Álvarez-Gil (2020); Bamford and Bondi (2005); Bondi (2017); Bondi and Sezzi (2016); Carrió-Pastor (2016); Gotti (2003Gotti ( , 2008; Halliday (1988Halliday ( , 1989Halliday ( , 1990; Hyland (2005Hyland ( , 2006Hyland ( , 2009; Hyland and Bondi (2006); Moskowich and Crespo (2014); Taavitsainen, Pahta and Mäkinen (2006), Taavitsainen and Pahta (2013) to mention but a few. This type of research may greatly benefit our understanding of contemporary discourse and authorship practices in different fields of knowledge.…”
Section: Introduction To the Monographic Section: Metadiscourse Devices In Academic Discoursementioning
confidence: 99%